Health systems strengthening for noncommunicable disease control and healthy aging: integrated actions in Aruba and Curaçao - Malhi Cho; Melissa Marchand; Enrique Vega; Reynaldo Holder; Silvana Luciani; Jeanine Constansia-Kook; José Moya (Pan American Health Organization, 2019)
Caribbean countries are experiencing social, epidemiological, and demographic transitions shaped by the growing elderly population and the rise of noncommunicable diseases (NCDs)now responsible for 78% of all deaths. These circumstances demand rethinking the model of care to improve health outcomes and build more sustainable health systems with new orientations in policy, service delivery, organization, training, technology, and financing. Policy must be aimed towards healthy living, leveraging interventions that ensure healthy aging. The health system must proactively structure interventions to reduce the incidence of new NCD cases and to prevent related complications. Interventions should be focused on optimizing the individuals capacity, functional ability, and autonomy within adapted environments, as well as with the necessary preventive, long-term care, self-care, community care, and health system support.